A single-blinded, randomized, parallel group superiority trial investigating the effects of footwear and custom foot orthoses versus footwear alone in individuals with patellofemoral joint osteoarthritis: a phase II pilot trial protocol - Narelle Wyndow; Kay M. Crossley; Bill Vicenzino; Kylie Tucker; Natalie J. Collins (Journal of Foot and Ankle Research, 2017)
Abstract Background Patellofemoral joint osteoarthritis is a common condition, yet information regarding conservative management is lacking. Foot orthoses are an effective intervention for improving pain and function in younger individuals with patellofemoral pain and may be effective in those with patellofemoral osteoarthritis. This pilot study will seek to establish the feasibility of a phase III randomised controlled trial to investigate whether foot orthoses worn in prescribed motion controlled footwear are superior to prescribed motion control footwear alone in the management of patellofemoral osteoarthritis. Methods/design This phase II pilot clinical trial is designed as a randomized, single-blind, parallel group, two arm, superiority trial. The trial will recruit 44 participants from Queensland and Tasmania, Australia. Volunteers aged 40 years and over must have clinical symptoms and radiographic evidence of patellofemoral osteoarthritis to be eligible for inclusion. Those eligible will be randomized to receive either foot orthoses and prescribed motion control shoes, or prescribed motion control shoes alone, to be worn for a period of 4 months. The feasibility of a phase III clinical trial will be evaluated by assessing factors such as recruitment rate, number of eligible participants, participant compliance with the study protocol, adverse events, and drop-out rate. A secondary aim of the study will be to determine completion rates and calculate effect sizes for patient reported outcome measures such as knee-related symptoms, function, quality of life, kinesiophobia, self-efficacy, general and mental health, and physical activity at 2 and 4 months. Primary outcomes will be reported descriptively while effect sizes and 95% confidence intervals will be calculated for the secondary outcome measures. Data will be analysed using an intention-to-treat principle. Discussion The results of this pilot trial will help determine the feasibility of a phase III clinical trial investigating whether foot orthoses plus motion control footwear are superior to motion control footwear alone in individuals with patellofemoral osteoarthritis. A Phase III clinical trial will help guide footwear and foot orthoses recommendations in the clinical management of this disorder. Trial registration Retrospectively registered with the Australian New Zealand Clinical Trials Registry: ACTRN12615000002583 . Date registered: 07/01/15.